2011
DOI: 10.1186/1471-2334-11-11
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with presentation to care with advanced HIV disease in Brussels and Northern France: 1997-2007

Abstract: BackgroundOur objective was to determine the frequency and determinants of presentation to care with advanced HIV disease in patients who discover their HIV diagnosis at this stage as well as those with delayed presentation to care after HIV diagnosis in earlier stages.MethodsWe collected data on 1,819 HIV-infected patients in Brussels (Belgium) and Northern France from January 1997 to December 2007. "Advanced HIV disease" was defined as CD4 count <200/mm3 or clinically-defined AIDS at study inclusion and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
42
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 42 publications
14
42
0
7
Order By: Relevance
“…For example, a large Swiss cohort study revealed that about 30% of patients diagnosed with CD4 T cell count below 200 cells/µl and even 10% with below 50 cells/µl [18]. The factors associated with late diagnosis in the Swiss study were increased age and non-Caucasian race, in line with observations from northern France and Brussels, Belgium [19]. The second factor with its potential implication can be excluded in regard of the presented population since only the Caucasian patients were evaluated.…”
Section: Discussionsupporting
confidence: 67%
“…For example, a large Swiss cohort study revealed that about 30% of patients diagnosed with CD4 T cell count below 200 cells/µl and even 10% with below 50 cells/µl [18]. The factors associated with late diagnosis in the Swiss study were increased age and non-Caucasian race, in line with observations from northern France and Brussels, Belgium [19]. The second factor with its potential implication can be excluded in regard of the presented population since only the Caucasian patients were evaluated.…”
Section: Discussionsupporting
confidence: 67%
“…Des études ont montré que le nombre de lymphocytes T CD4 à la mise sous TARV est le plus important facteur pré-dictif de la progression de la maladie, notamment des complications infectieuses et de la survie des patients après la mise sous TARV (24). Le taux médian de CD4 dans cette étude à la mise sous TARV était de 177 cellules/mm 3 et on notait que 56,4 % des patients mis sous TARV à la période d'étude l'avaient initié avec des CD4 inférieurs à 200 cellules/mm 3 .…”
Section: Discussionunclassified
“…En Afrique de l'Ouest, Bashi et al avaient retrouvé 139 cellules/mm 3 (3) tandis que Mouhari-Touré notait 138 cellules/ mm 3 en 2009 (22). Cela pose le problème du diagnostic et celui de la prise en charge tardive des patients en Afrique subsaharienne, expliquant la mortalité initiale très élevée à la mise sous TARV (24). Par contre dans les pays dévelop-pés, l'initiation du TARV est relativement plus précoce.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estadísticas señalan que entre 22 y 83% de las personas infectadas por VIH fueron diagnosticadas en etapa de SIDA en Europa y Estados Unidos de Améri-ca [2][3][4][5][6] . Esta tendencia se mantiene en Chile, en el año 2008, 9.193 personas fueron diagnosticadas en etapa de SIDA 7 , representando 46% de las infectadas por VIH 8 .…”
Section: Introductionunclassified